Cardiovascular structure and function assessed by MRI in healthy South Asians compared to White Europeans: a UK Biobank study. (3rd October 2022) - Parke, K; Gulsin, G; Singh, A; Arnold, R; Ayton, S; Dattani, A; Yeo, J; McCann, G; Brady, E
Abstract: Background: There is limited data on ethnic specific comparisons for measures of cardiovascular structure and function in healthy cohorts. Echocardiographic data indicate South Asian's (SAs) have smaller mass and evidence of more concentric remodelling compared to White Europeans (WEs). Furthermore, there is no data published for strain or strain rates. Purpose: To compare Cardiac Magnetic Resonance (CMR) derived measures of structure and function between age and sex matched healthy SAs and WEs from the UK biobank cohort. Methods: South Asian and WE participants from the UK Biobank who underwent CMR imaging were included. Individuals with a history of cardiovascular disease, hypertension, obesity (BMI ≥30 kg/m 2 in WEs and ≥27 kg/m 2 in SAs) and diabetes were excluded. Ethnic groups were matched according to age and sex at recruitment. Cine images (bSSFP) were analysed blinded to participant details using commercially available software. Left ventricular (LV) mass, LV volumes, global longitudinal and circumferential systolic strain (GLS and GCS), together with peak early diastolic strain rates (PEDSR), were obtained. Data distributions were assessed and T-Test or Man Whitney U conducted as appropriate. Results: Datasets from the UK biobank were screened (n=45000). After applying exclusion criteria, 111 pairs of matched SAs and WEs were available for analysis (n=69 male and n=42 female matched pairs). Mean age of the entire cohort was 58±8 years. Data has been corrected according to body surface area (BSA), (males: WE 2.0±0.1 vs SA 1.8±0.1 m 2, p≤0.001; females: WE 1.7±0.2 vs SA 1.6±0.1 m 2, p≤0.001). There was no difference in heart rate (males: WE 64.5±9.3 vs SA 65.8±9.6 bpm, p=0.113; females: WE 66.2±7.8 vs SA 69.5±10.3 bpm, p=0.125). Results by sex and ethnicity are displayed in table 1. In males there was no difference in ejection fraction (EF) or indexed LV end diastolic volume (LVEDV). However indexed mass and mass/volume ratio were significantly lower in SAs, and GLS but not GCS was significantly higher than in SAs. Longitudinal PEDSR were significantly higher in SAs than in WE. By contrast, SA females had significantly lower EF with no difference in indexed LVEDV compared to WE females. However, as seen with the males SA females had significantly lower indexed LV mass and mass/volume ratio compared to WE females. Finally, both GLS and GCS were significantly higher in SAs compared to WE females, whereas there was no difference in longitudinal PEDSR. Conclusion: Substantial differences in cardiovascular structure and function exist between SA and WE ethnic groups, in both men and women. Contrary to previous echocardiographic studies, LV volumes were similar between ethnicities and SA have less, not increased, concentric remodelling than WE. These findings highlight the need for ethnicity and sex-specific healthy reference ranges derived from CMR. Funding Acknowledgement: Type of funding sources: None.